Legal Aspects of Company Establishment in the Field of Coal Transportation and Sales Business After the Enactment of Law Number 3 Of 2020 Concerning Amendments to Law Number 3 of 2009 Concerning Mineral and Coal Mining - May Kurniawan Sanjaya; Fully Handayani Ridwan (IHSA Institute, 2022)
This research will examine the aspects of forming a business entity or company and the factors that must be considered when establishing a company in the coal transportation and sales industry. The purpose of this article is to investigate the concept of the structure of a company entity in Indonesian laws and regulations, as well as the legal factors that must be considered when establishing coal transportation and sales company. However, the permits must be consistent with the activities to be conducted to engage in continuous business activities and generate profits. The company's legality must be considered when establishing a company in the coal transportation and sales industry, particularly in the KBLl 2020 business field with code 46610. After obtaining a Transportation and Sales Business Permit, the company could sell coal commodities.